THE EFFECT OF UTILIZATION OF ACCOUNTING INFORMATION SYSTEMS AND INTERNAL CONTROL ON COMPANY PERFORMANCE (CASE STUDY ON STATE-OWNED COMPANIES IN EAST JAVA) - Muhammad Hamas Albarra; Suwandi Suwandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effect of Accounting Information Systems (AIS) and Internal Control (PI) on company performance, with a case study of BUMN Companies in East Java. The research uses a descriptive quantitative approach with primary data obtained through questionnaires and interviews. The data were analyzed using multiple linear regression, as well as classical assumption tests to ensure the validity and reliability of the model. The results showed that AIS has a positive and significant effect on company performance, as evidenced by a significance value of 0.035 (<0.05). AIS supports operational efficiency, reporting accuracy, and strategic decision making, thus contributing directly to performance improvement. In contrast, PI has no significant effect on company performance, with a significance value of 0.952 (>0.05). This indicates that the effectiveness of internal control may be limited by other variables that are more dominant, or the implementation is not yet optimal.